Influence of plant and environment parameters on phytochemical composition and biological properties of Pistacia atlantica Desf. (April 2021) - Benmahieddine, Assia; Belyagoubi-Benhammou, Nabila; Belyagoubi, Larbi; El Zerey-Belaskri, Asma; Gismondi, Angelo; Di Marco, Gabriele; Canini, Antonella; Bechlaghem, Nadjat; Atik Bekkara, Fawzia; Djebli, Noureddine
Abstract: The aim of the current study is to analyze the phytochemical, antioxidant and antimicrobial activities of 34 extracts prepared from Pistacia atlantica Desf. subsp. atlantica, according to gender, organ type (roots, buds and fruits), geographical location and stage of ripening. Bud extracts exhibited the highest phenolic content (565.74 ± 9.84 mg GAE/g DM), followed by fruit and root extracts. TFC and TTC ranged from 0.38 ± 0.03 to 1.92 ± 0.11 mg CE/g DM and from 0.37 ± 0.03 to 16.54 ± 0.94 mg CE/g DM, respectively. For DPPH and TAC assays, the values varied from 0.038 ± 0.000 to 1.331 ± 0.114 mg/mL and 1.58 ± 0.06 to 43.64 ± 2.58 mg AAE/g DM, respectively. Besides, bud extracts showed the highest bioactivity against pathogenic bacteria and a slight antifungal effect. Additionally, HPLC-DAD analysis revealed that the caffeic acid and the dimethyl-allyl caffeic acid characterized the bud extract, while the rutin and the hydroxytyrosol were abundant in the red fruit extract. The present evidence suggests that P . atlantica may be considered as a potential source of new additives for therapeutic, food and cosmetic products. Highlights: Preparation of 34 extracts from roots, leaf-buds and fruits of Pistacia atlantica Desf. subsp. atlantica. Assessment of the variation of phenolic, flavonoid and condensed tannin. Antioxidant capacity of these extracts. Antimicrobial activity and HPLC analysis of crude extract of leaf-buds and red fruits.